Water, agriculture and poverty in the Niger River Basin - Ogilvie, A.; Mahe, G.; Ward, J.; Serpantie, G.; Lemoalle, J.; Morand, P.; Barbier, Bruno; Diop, Amadou Tamsir; Caron, A.; Namara, Regassa E.; Kaczan, D.; Lukasiewicz, A.; et al. (Informa UK Limited, 2010)
Livelihoods in the Niger River basin rely mainly on rainfed agriculture, except in the dry extreme north. Low yields and water productivity result from low inputs, short growing seasons, dry spells, and excessive water. The overlap of traditional and modern rules impedes secure access to water and investments in agriculture by generating uncertain land tenure. Improved agriculture and water management require technical, sociological, and regulatory changes to address the wider causes of poverty. Illiteracy and poor water quality, both correlated with high infant mortality, are pressing problems. Rapidly increasing population, climatic changes and dam construction contribute to rural vulnerability.